OPTIMIZATION OF UHPLC METHOD FOR QUANTIFYING IBRUTINIB AND ITS PROCESS-RELATED IMPURITIES IN API: UTILIZING BOX-BEHNKEN DESIGN - KRISHNARAJU, KALPANA; VELRAJ, MALARKODI (International Journal of Applied Pharmaceutics, 2025)
Objective: The objective of this work was to create, refine, and verify a reliable ultra-performance liquid chromatography (UPLC) technique for ibrutinib and its impurity analysis. The novelty of the work lies in the systematic application of a two-phase optimization approach, combining initial screening with Design of Experiments (DoE), to achieve superior chromatographic performance, enhanced sensitivity, and robust resolution metrics. Methods: The method development involved two phases: (1) an initial screening phase to evaluate critical parameters, including the stationary phase, mobile phase substance, the pH, the flow rate, and the column temperature (2) a DoE phase using a Box-Behnken design to optimize these parameters. Five columns and three mobile phases were tested, with the ACQUITY UPLC® BEH the optimum conditions were determined to be a C18 column with a mobile phase of 0.02 M formic acid in a 50:50 v/v mixture of water and acetonitrile at pH 2.7. To assess the impacts of predictor factors (mobile phase pH, the flow rate, and the column temperature) on retention duration, resolution, and peak separation, quadratic models developed from ANOVA analysis were employed. The technique was verified according to ICH requirements, assessing system appropriateness, specificity, linearity, precision, accuracy, solution stability, and robustness. Results: The optimized UPLC method achieved a resolution of 4.66 between ibrutinib and Impurity-I, with retention times of 2.64 min (ibrutinib) and 4.40 min (last eluting peak). Sensitivity was high, with LOD and LOQ values are 0.01 μg/ml and 0.025 μg/ml, respectively, for ibrutinib, and similar sensitivity for impurities. Linearity was excellent (correlation coefficients ≥ 0.9996), ranging from 0.025 to 100 μg/ml (ibrutinib) and 0.025 to 0.225 μg/ml (impurities). Precision (% RSD<2% for ibrutinib,<10% for impurities) and accuracy (recovery 93.58–104.75%) met ICH criteria. Robustness testing under varied conditions confirmed method reliability, ensuring compliance with regulatory standards for pharmaceutical quality control. Conclusion: The UPLC method, optimized via Box-Behnken design, provides a sensitive, precise, and robust tool for quantifying ibrutinib and its impurities. Systematic optimization enhanced resolution, sensitivity, and robustness, ensuring regulatory compliance and supporting pharmaceutical quality control. This advancement enables reliable impurity profiling and accurate drug quantification.